PENGARUH PENGGUNAAN FLIPBOOK BERBASIS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP PENALARAN MATEMATIS PESERTA DIDIK KELAS VIII UPTD SMP NEGERI 1 KEC. GUGUAK - Asra, Aqilul; Suherman, Suherman (Departemen Matematika, 2024)
The development of reasoning skills is very important for students, because without reasoning skills, mathematics will only be an exercise to follow methods and imitate examples, without understanding. This study aims to assess whether mathematical reasoning skills will be superior using CTL-based flipbooks compared to conventional teaching materials in class VIII UPTD SMP Negeri 1 Kec. Guguak in TP 2023/2024. The research methodology applied was Quasi Experiment, and the design chosen was Nonequivalent Posttest-Only Control Group Design. The results prove that students' mathematical reasoning skills are superior when they are taught using flipbooks based on the Contextual Teaching and Learning approach, in class VIII UPTD SMP Negeri 1 Kec. Guguak.Keywords. – Mathematical Reasoning Ability, flipbook, Contextual Teaching and Learning approach